Ugotavljanje in razvijanje ključnih področij usposobljenosti (kompetenc) zdravnikov kot izhodišče za modernizacijo izobraževalnega programa - Pavlin, Samo (Zdravstveno varstvo, 2008)
Objective: To determine to what extent the general medicine training programme at the Faculty of Medicine, University of Ljubljana, Slovenia, impacts the development of key competences of future medical doctors. Methods: Analysis of relevant literature on key competences; expert workshop with the focus group of 'the best students' (N=9) in the last two years at the Faculty of Medicine in Ljubljana. Results: The survey results showed that training in general medicine at the Ljubljana Faculty of Medicine does not prepare students adequately for providing motivation and guidance to their patients, to feel empathy with some preservation of emotional distance, to manage team work and to master communication skills. Conclusions: General medicine training programme offered at the Ljubljana Faculty of Medicine should place greater focus on the development of situation-related competences and socialization of students. This goal can be achieved by enriching the present curriculum with new specialized subjects and by integrating new teaching modules into current teaching practices.
Keywords: kompetence; Slovenia; Slovenija; splošna medicina; študijski programi; usposobljenost